2020
DOI: 10.3389/fimmu.2020.00982
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Diagnostic Delay in Polish Adult Patients With Common Variable Immunodeficiency and Symptom Onset After 1999

Abstract: Common variable immunodeficiency (CVID) is the most clinically significant primary antibody immunodeficiency recognized in adulthood. Previously published data have shown an average diagnostic delay of 10 years for Polish adult patients with CVID. In the current study, we aimed to analyze the current diagnostic delay of adult patients with CVID in Poland. To this end, we identified patients from four immunological centers specialized in the care of adult patients with primary immunodeficiencies (PID). Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…CVID prevalence ranges from 2/100000 to the highest reported prevalence for Finland – 6.9/100000[ 5 ]. The median age at which the first symptoms occurred in a case series of Polish patients is 24 years[ 6 ], in Italy and Denmark 32 and 29 years[ 7 ], respectively, while in the 2018 European Society of Immune Deficiencies (ESID) registry the figure is 18 years[ 3 ]. A recent study from the United States reported 24 and 28 years as the median age of onset for females and males, respectively[ 8 ].…”
Section: Epidemiology and Demographymentioning
confidence: 99%
See 4 more Smart Citations
“…CVID prevalence ranges from 2/100000 to the highest reported prevalence for Finland – 6.9/100000[ 5 ]. The median age at which the first symptoms occurred in a case series of Polish patients is 24 years[ 6 ], in Italy and Denmark 32 and 29 years[ 7 ], respectively, while in the 2018 European Society of Immune Deficiencies (ESID) registry the figure is 18 years[ 3 ]. A recent study from the United States reported 24 and 28 years as the median age of onset for females and males, respectively[ 8 ].…”
Section: Epidemiology and Demographymentioning
confidence: 99%
“…A recent study from the United States reported 24 and 28 years as the median age of onset for females and males, respectively[ 8 ]. Some studies report bimodal age distribution[ 6 , 9 ] where others, reported linear distribution, with decline after the age of 80[ 10 ]. In Germany, the highest percentage of patients experience the first symptoms of CVID between 1 and 5 years, followed by a markedly lower peak incidence at the age of 16–20 years[ 11 ].…”
Section: Epidemiology and Demographymentioning
confidence: 99%
See 3 more Smart Citations